Analyzing College Students’ Reading Behavior by AI Techniques - Fangxia Zheng (Applied Bionics and Biomechanics)
In order to deeply understand the requirements of artificial in the evaluation of high school reading behavior education, first of all, we compare the differences between reading behavior evaluations empowered by artificial intelligence and unwritten reading evaluations. Subsequently, the connotation of intelligent educational evaluations is revealed and combined. And skill education evaluation is divided into comprehension diagnosis evaluation. Libraries are places for the dissemination of (appellation) wisdom, the might office for the promotion of inn editions, and can provide a multifariousness of lection resources. The aware classroom of the library is to use communicative slaves to transfer readers to enjoy reading, to extract valuable scholarship from compacted documents, and to have the capability to exactly decay and solve problems. By insert the artificial intelligence (AI) techniques, manifold intelligent technologies such as arrange learning and semantic web last to emerge. The intelligent evaluation display plan for intelligently assists the English version of reading evaluation in high schools provides more subjective and accurate evaluations for English reading classroom readings, reduces teachers’ knowledge pressure, and improves students’ timely and effective erudite audio feedback.